Workplace Ostracism and Contextual Performance: The Moderating Effects of Self-Efficacy - Bhatt, Bhumi; Rana, Neeti (Gyan Management Journal, 2023)
Organizational isolation is different from social isolation. The social isolation could be due to society or the indi vidual isolating Williams, (1997) from social activities. Similar to that the organizational isolation could be due to  the factors which prevail in the work environment or it could be due to the individual working in that situation.  The reasons and the influencing factors are really hard to determine as we could find individuals feeling that they  are secluded and isolated and ignored in work and work situations and their challenges. It also indicates that there  is a need for support and helps to be provided to these employees and if left unattended would lead to depression  Fowler, Wareham-Fowler & Barnes, (2013) and counterproductive behavior. The consequence of this WPO is that  employee does not feel associated or related to the organization anymore as the Ferris, Brown, Berry &Lian, (2008)  sense of isolation and psychological depression seem to prevail more. This could also become a mass phenomenon  as this sense of isolation and depression could spread to other employees as well which indicates the seriousness  of the issue. The factors of culture, religion, and ethnic diversity, Nezlek et al (2012) cross-cultural workplace and  dynamics could lead to ostracism in workplace situations. As these dimensions and issues have implications for  organizational development, human psychology & workplace performance it is an important dimension to be  studied, evaluated, and assessed. The factors which lead to organizational ostracism have been evaluated and pro vided as abusive supervision, Wu, Wei & Hui, (2011) voice behavior, and supervisory support. Organizational sup port is helpful in mitigating organizational stress and workplace ostracism Anjum, Ming, Siddiqi & Rasool, (2018).
Keywords: Workplace; Ostracism; Contextual Performance; Moderating Effects; Self-Efficacy